INTERPRETASI SURAH AN-NAS OLEH MUHAMMAD ISMAIL AL-ASCHOLY (SEBUAH ANALISIS TERHADAP TAFSIR LISAN DALAM KAJIAN “NGAJI TAFSIR ALA NU BERSAMA LORA ISMAIL AL-ASCHOLY) - ,, Muzayyin; ,, Mazidaturrofi’ah; Fakhrurrozi, Achmad Wafiq (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2025)
Contemporary Quranic exegetes increasingly utilize social media as a medium to disseminate their interpretations to wider and more diverse audiences. One prominent figure in this trend is Muhammad Ismail Al-Ascholy, a young scholar from Bangkalan, Madura. He actively shares his insights through Instagram’s Instastory feature via his account @ismailascholy, and frequently employs platforms such as YouTube, Zoom Meetings, and Instagram Live to deliver oral exegeses.This study aims to highlight the dynamic nature of oral approaches to Quranic interpretation in the contemporary context and to examine the distinctive features of Al-Ascholy’s oral exegesis of Surah An-Nas, as presented in the Ngaji Tafsir Ala NU x Lora Ismail Al-Ascholy program on the Ala NU channel.This research adopts a descriptive-qualitative approach, drawing upon Andreas Gorke’s theory of oral interpretation, complemented by Walter J. Ong’s concept of orality. The findings highlight the distinctive features of orality in the works of Al-Ascholy, with a particular focus on the repetition of verses at the conclusion of Surah An-Nas and the profound threats conveyed therein.This study concludes that presenting oral interpretations via social media can serve as an alternative medium for contemporary exegetes to actively engage with and contribute to the evolving landscape of Qur'anic interpretation.